Survival and complications of single dental implants in the edentulous mandible following immediate or delayed loading: A randomized controlled clinical trial - Priya Nagar; Krishan Yadav; Shaikh Mohammad Abdul Feroz; Praveen Gangadharappa; Utkarsh Gupta; Jeevanandam Loganathan (Wolters Kluwer Medknow Publications, 2023)
Introduction: The lifespan of an edentulous mandible with one median implant to hold a full denture for 24 months was evaluated to see if the early loading had any impact on it. Single-implant denture retention for the mandibular region was proposed by "Cordioli et al. in the 1990s. Objectives: Whether rapid loading and placement of a "single median implant" may result in the implant survival rate comparable to rehabilitation with a single implant and second-stage surgery. Methods: It was found that 81 of the 158 implant recipients had quick loading, whereas the rest had delayed loading (77 patients). Patients in the context of "delayed loading group" had follow-up appointments at 1 month, 4 months, 12 months, and 24 months. In addition, the nine implants failed in the 3 months after loading in a quick loading group, while just one implant failed before loading. Median implant survival at 2 years was the study's main goal. Direct loading had a 7% fatality rate advantage over traditional loading because of the alleged advantages of immediate loading, including the avoidance of second-stage surgery. Prosthetic problems were evaluated using Fisher's exact test. Results: A higher rate of implant survival was not seen when implants were loaded more quickly (P = 0.81). A statistically significant difference (P = 0.019) was seen in implant survival between the therapy groups. Conclusion: Single implant loading in an edentulous mandible has a worse survival rate than delayed loading, according to all available research.